2003
DOI: 10.1080/10417940309373260
|View full text |Cite
|
Sign up to set email alerts
|

Relational implications of communication skill evaluations and love styles

Abstract: Abstract:As values placed by individuals on communication skills may associate with experiences of romantic love, this study explores relationships between communication values and the adoption of six major love styles (Lee, 1973). Two hundred and seventy-two participants (119 males and 153 females) completed an expanded version of Burleson and Samter's (1990) Communication Functions Questionnaire, which generates judgments about the importance of several communication skills, and Hendrick and Hendrick's (198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…A number of studies reported that women favored the style of Agape more than men (e.g., Davies, 2001;Schultz et al, 2001). In contrast, other research indicated men scored higher on Agape (e.g., Fallon & Bowles, 1999;Grote & Frieze, 1998;Heaven, Da Silva, Carey, & Holen, 2004;Kunkel & Burleson, 2003;Sprecher & Toro-Morn, 2002;Worobey, 2001). The inconsistencies in these results may be due to the fact that most love-style studies were conducted to contrast and compare different love styles and did not focus on one style of love.…”
Section: Marriage and Family Reviewmentioning
confidence: 59%
“…A number of studies reported that women favored the style of Agape more than men (e.g., Davies, 2001;Schultz et al, 2001). In contrast, other research indicated men scored higher on Agape (e.g., Fallon & Bowles, 1999;Grote & Frieze, 1998;Heaven, Da Silva, Carey, & Holen, 2004;Kunkel & Burleson, 2003;Sprecher & Toro-Morn, 2002;Worobey, 2001). The inconsistencies in these results may be due to the fact that most love-style studies were conducted to contrast and compare different love styles and did not focus on one style of love.…”
Section: Marriage and Family Reviewmentioning
confidence: 59%
“…Sample items include: "My partner fits my ideal standards of physical beauty" (eros), "I enjoy playing the 'game of love' with my partner and a number of other partners" (ludus), "Our friendship merged gradually into love over time" (storge), "One consideration in choosing my partner was how he/she would reflect on my career" (pragma), "When my partner does not pay attention to me, I feel sick all over" (mania), and "I would rather suffer myself than let my partner suffer" (agape). Previous reliability coefficients for this scale have been: .71 for the Eros subscale, .69 Ludus, .75 Storge, .78 Pragma, .74 Mania, and .82 Agape (Kunkel & Burleson, 2003). In this study, obtained Cronbach coefficients alpha were: Eros (α = .74), Ludus (α = .83), Storge (α = .77), Pragma (α = .81), Mania (α = .75), and Agape (α = .84).…”
Section: Methodsmentioning
confidence: 98%
“…People who have a PLA prefer spending time with their partners as well as giving and receiving tokens of affection, such as comforting and supporting their partner, managing conflicts, and helping their partner resolve issues. 35 These people are attentive and expressive in face-to-face interactions because of their positive perceptions of self and others. 36 Partners who score high in PLA are likely to be highly competent in communication and in managing a high-quality relationship.…”
Section: Rq2: How Does Communication Quality Online Mediate the Relationships Between Mobile-mediated Communication And Relationship Qualmentioning
confidence: 99%